On relation between the autoemitter top field, anode voltage and cathode geometry - Stetsenko, B.V.; Shchurenko, A.I. (Вопросы атомной науки и техники, 2009)
A field emission diode has been made up on the basis of a flat metal anode and pin cathode (of the height a) that is
mounted on a flat metal plate parallel to the anode. The potential of the field emission diode has been calculated as the
function of the pin cathode shape, its height, the anode-cathode potential and the potential value into cathode. It has
been shown that the potential barrier transparency possesses a nonlinear dependence on the anode potential in the
Fowler-Nordheim coordinates, if the cathode height (a) is less than 1000 nm. To obtain a measurable field emission
current, the following condition should be met: Fmid·a>φ, were Fmid is the macroscopic field strength within the anodecathode
spacing, and φ is the pin cathode work function. Therefore, to get the field emission current, either the field
strength should be >10⁶ V/cm, or another field source should be used in addition. For example, the contact electrode
potential between the pin part of the cathode and its base can provide such a field source. An analytic function was
derived for the electric field of a pin cathode located on a flat substrate. Розрахований потенціал автоемісійного діоду. Показано, що при зменшенні висоти вістря катоду
(<1000 нм) прозорість потенційного бар’єру залежить в координатах Фаулера-Нордгейма нелінійно від анодної
напруги. Необхідною умовою автоемісії є нерівність Fmid·a>φ, де Fmid – величина макроскопічного поля, а φ –
робота виходу катоду. Отже, для одержання автоемісійного струму з вістрів необхідно чи велике середнє поле
між електродами (>10⁶ В/см), чи додаткові до зовнішнього джерела поля. Таке поле може створюватися
контактною різницею потенціалів між підкладкою і вістрям. Одержана аналітична формула для потенціалу
електричного поля. Рассчитан потенциал автоэмиссионного диода. Показано, что при уменьшении высоты острия катода
(<1000 нм) прозрачность потенциального барьера зависит в координатах Фаулера-Нордгейма нелинейно от
анодного напряжения. Необходимым условием автоэмиссии является неравенство Fmid·a>φ, где Fmid – величина
макроскопического поля, а φ – работа выхода катода. Таким образом, для получения автоэмиссионного тока из
остриев необходимо либо высокое среднее поле между электродами (>10⁶ В/см), либо дополнительные к
внешнему источники поля. Такое поле может создаваться контактной разностью потенциалов между
подложкой и острием. Получена аналитическая формула для потенциала электрического поля.